Research of Function Optimization Algorithm - Qinghua Wu; Hanmin Liu; Yuxin Sun; Fang Xie; Jin Zhang; Xuesong Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Traditional evolutionary algorithm trapped into the local minimum easily. Therefore, based on a simple evolutionary algorithm and combine the base ideology of orthogonal test then applied it to the population initialization, crossover operator, as well as the introduction of Inver-Over operator to prevent local convergence to form a new evolutionary algorithm. Through the series of numerical experiments, the new algorithm has been proved is efficiency for function optimization. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.877